Effects of polishing techniques on the staining of two nano-tooth coloured materials - Teo, Kui Fei; Zuryati Ab-Ghani,; Zaid Hameed Mohammed Ali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Surface polishing affect the staining of nano-tooth coloured materials. Here we studied the effect of tea and coffee staining on polished nano-composite resin and nano-ormocers. Eighty-four discs (5 × 2 mm) of Filtek Z350 and Ceram X were fabricated using acrylic molds and polished with either: (1) Sof-lex (2) Enhance/Pogo (3) control (no polishing-Mylar). After polishing, the tests materials were immersed in either tea or coffee (n=7), for 48, 96 and 168 h at 37°C. The colour difference (ΔE) values were assessed with a spectrophotometer (Cecil CE 2021 UV/VIS), the data were analysed using Kruskal-Wallis Test. The results showed that polishing significantly affected the ΔE values of both materials (p<0.05). In all groups, Ceram X showed less staining than Filtek Z350. Both Filtek Z350 and Ceram X also reacted differently in coffee and tea. Significant ΔE values for Filtek Z350 obtained with different polishing techniques exposed to coffee in ascending order: Sof-lex < Enhance/Pogo < Mylar strip. For Ceram X, significant ΔE values obtained in exposure to tea in ascending order: Pogo < Mylar < Sof-lex. Mylar caused more staining in Filtek Z350 whilst Sof-Lex caused the least staining. However, in Ceram X, Enhance/Pogo caused the least staining. In conclusion, Ceram X is more colour stable than Filtek Z350. It may be suggested to always use the polishing system produced by the same company that produces the restorative material for better staining resistant.